The redundancy of positivism as a paradigm for nursing research - Corry, Margarita (Nursing philosophy, 2019)
New nursing researchers are faced with a smorgasbord of competing methodologies. Sometimes, they are encouraged to adopt the research paradigms beloved of their senior colleagues. This is a problem if those paradigms are no longer of contemporary methodological relevance. The aim of this paper was to provide clarity about current research paradigms. It seeks to interrogate the continuing viability of positivism as a guiding paradigm for nursing research. It does this by critically analysing the methodological literature. Five major paradigms are addressed: the positivist; the interpretivist/constructivist; the transformative; the realist; and the postpositivist. Acceptance of interpretivist, transformative or realist approaches necessarily entails wholesale rejection of positivism, while acceptance of postpositivism involves its partial rejection. Postpositivism has superseded positivism as the guiding paradigm of the scientific method. The incorporation in randomized controlled trials of postpositivist assumptions indicates that even on the methodological territory that it once claimed as its own, positivism has been rendered redundant as an appropriate paradigm for contemporary nursing research.